The Economic Impact of Tourism in Nepal - Simkhada, Menuka (Nepalese Journal of Finance, 2024)
This study examines the economic impact of tourism in Nepal. Gross domestic product is the dependent variable. The selected independent variables are foreign exchange earnings from tourism, government revenue from tourism, business revenue from tourism, online ticketing, tourist activity and gross domestic products. The primary sources of data is used to assess the opinions of respondents regarding foreign exchange earnings from tourism, government revenue from tourism, business revenue from tourism, online ticketing, tourist activity and gross domestic products. The study is based on primary data of 113 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of the economic impact of tourism in Nepal. The study showed that foreign exchange earning form tourism is positively correlated to gross domestic product. It indicates that increase in foreign exchange earning form tourism leads to increase in gross domestic product. Similarly, government revenue from tourism is positively correlated to gross domestic product. It indicates that increase in government revenue from tourism leads to increase in gross domestic product. Likewise, business revenue from tourism is positively correlated to gross domestic product. It indicates that increase in business revenue from tourism leads to increase in gross domestic product. Further, online ticketing is positively correlated to gross domestic product. It indicates that higher the number of ticket booking from online leads to increase in gross domestic product. In addition, tourist activity is positively correlated to gross domestic product. It indicates that increase in tourist activity leads to increase in gross domestic product.